How do you find (g@f)(-2+x) given g(x)=2x-2 and f(x)=x^2+3x?

1 Answer
Aug 19, 2016

2x^2-2x-6

Explanation:

The first step is to find an expression for (g ○ f ), which can also be written as g(f(x)).

To do this substitute x = f(x) into g(x)

rArrg(f(x))=g(color(red)(x^2+3x))=2(color(red)(x^2+3x))-2

rArrg(f(x))=2x^2+6x-2

To evaluate (g ○ f)(-2 +x) substitute x = - 2 +x into g(f(x))

rArr(g(f(color(magenta)(-2+x)))=2(color(magenta)(-2+x))^2+6(color(magenta)(-2+x))-2

=2(4-4x+x^2)-12+6x-2

=8-8x+2x^2-12+6x-2=2x^2-2x-6